Analisis Dampak Pembangunan Infrastruktur Terhadap Kemiskinan Di Kawasan Teluk Tomini - Rachman, Fadilla Garini; Arham, Muhammad Amir; Dai, Sri Indriyani S; Santoso, Ivan Rahmat (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study was to determine the effect of road, water and electricity infrastructure development on poverty in the Tomini Bay area. The type of research used is quantitative with multiple linear regression analysis methods. From the results of multiple linear regression analysis, it can be concluded that road infrastructure has a positive and significant effect on poverty. This means that every 1 percent increase in road infrastructure will increase poverty in the Tomini Bay area. Electricity Infrastructure has a negative and significant effect on Poverty. This means that every 1 percent increase in Electricity Infrastructure will reduce Poverty in the Tomini Bay Area. Water Infrastructure has a positive and significant effect on Poverty. This means that every 1 percent increase in Water Infrastructure can increase Poverty in the Tomini Bay Area.